Nano-crystalline ceramic laser materials and lasers - Gong, Hua (2011)
Polycrystalline transparent yttrium aluminum garnet (YAG) ceramics is an excellent host material for high-power solid-state lasers. Compared to its single crystal form, polycrystalline YAG transparent laser ceramics have the advantages of faster production times, ease fabrication of large size, high dopant concentration, mass production and multifunctionality. Therefore, YAG transparent ceramics has become a very active research topic in the field of advanced ceramics. In this work, YAG, rare-earth ions doped YAG and Y2O3 nanosized powders have been synthesized by general and modified sol-gel combustion process, co-precipitation assisted with freeze-drying, and high-energy ball milling method, respectively. Highly transparent Nd:YAG ceramics with good lasing quality have been fabricated. Phase evolution, morphology and microstructure of the nanopowders and transparent ceramics were investigated. Key effects on optical properties of the fabricated ceramics were also systematically studied. Our results show that solvent has an important effect on the phase transformation temperature of sol-gel precursor. Ethanol-deionized water (volume ratio of 1:1) mixture solution adopted as solvent can effectively decrease activation energy, leading to YAG formation at lower calcination temperature. However, the residue carbonates is difficult to be removed completely. As a result, there are many pores trapped in the sintered YAG ceramics. It was found that high energy ball milling can significantly promote YAG phase transformation by solid-state reactive sintering using Y2O3 and Al2O3 nanosized powders as starting materials.